Genotyping of major histocompatibility complex Class II DRB gene in Rohilkhandi goats by polymerase chain reaction-restriction fragment length polymorphism and DNA sequencing - Shrivastava, Kush (Vet World, 2015)
AIM: To study the major histocompatibility complex (MHC) Class II DRB1 gene polymorphism in Rohilkhandi goat using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and nucleotide sequencing techniques. MATERIALS AND METHODS: DNA was isolated from 127 Rohilkhandi goats maintained at sheep and goat farm, Indian Veterinary Research Institute, Izatnagar, Bareilly. A 284 bp fragment of exon 2 of DRB1 gene was amplified and digested using BsaI and TaqI restriction enzymes. Population genetic parameters were calculated using Popgene v 1.32 and SAS 9.0. The genotypes were then sequenced using Sanger dideoxy chain termination method and were compared with related breeds/species using MEGA 6.0 and Megalign (DNASTAR) software. RESULTS: TaqI locus showed three and BsaI locus showed two genotypes. Both the loci were found to be in Hardy–Weinberg equilibrium (HWE), however, population genetic parameters suggest that heterozygosity is still maintained in the population at both loci. Percent diversity and divergence matrix, as well as phylogenetic analysis revealed that the MHC Class II DRB1 gene of Rohilkhandi goats was found to be in close cluster with Garole and Scottish blackface sheep breeds as compared to other goat breeds included in the sequence comparison. CONCLUSION: The PCR-RFLP patterns showed population to be in HWE and absence of one genotype at one locus (BsaI), both the loci showed excess of one or the other homozygote genotype, however, effective number of alleles showed that allelic diversity is present in the population. Sequence comparison of DRB1 gene of Rohilkhandi goat with other sheep and goat breed assigned Rohilkhandi goat in divergence with Jamanupari and Angora goats.